Recirculation in single lumen cannula venovenous extracorporeal membrane oxygenation: A non-randomized bi-centric trial - Fisser, Christoph; Palmér, Oscar; Sallisalmi, Marko; Paulus, Michael; Foltan, Maik; Philipp, Alois; Malfertheiner, Maximilian V.; Lubnow, Matthias; Müller, Thomas; Broman, Lars Mikael (Frontiers in Medicine, 2022)
Background: Recirculation is a common problem in venovenous (VV) extracorporeal membrane oxygenation (ECMO). The aims of this study were to compare recirculation fraction (Rf) between femoro-jugular and jugulo-femoral VV ECMO configurations, to identify risk factors for recirculation and to assess the impact on hemolysis. Methods: Patients in the medical intensive care unit (ICU) at the University Medical Center Regensburg, Germany receiving VV ECMO with femoro-jugular, and jugulo-femoral configuration at the ECMO Center Karolinska, Sweden, were included in this non-randomized prospective study. Total ECMO flow (QEC), recirculated flow (QREC), and recirculation fraction Rf=QREC/QEC were determined using ultrasound dilution technology. Effective ECMO flow (QEFF) was defined as QEFF=QEC*(1–Rf). Demographics, cannula specifics, and markers of hemolysis were assessed. Survival was evaluated at discharge from ICU. Results: Thirty-seven patients with femoro-jugular configuration underwent 595 single-point measurements and 18 patients with jugulo-femoral configuration 231 measurements. Rf was lower with femoro-jugular compared to jugulo-femoral configuration (5 [0; 11] vs. 19 [13; 28] %, respectively (p<0.001)), resulting in similar QEFF (2.80 [2.21; 3.39] vs. 2.79 [2.39; 3.08] L/min (p=0.225)) despite lower QEC with femoro-jugular configuration compared to jugulo-femoral (3.01 [2.40; 3.70] vs. 3.57 [3.05; 4.06] L/min, respectively, (p<0.001)). In multivariate regression analysis, the type of configuration, distance between the two cannula tips, ECMO flow, and heart rate were significantly associated with Rf (B [95%-CI]: 25.8 [17.6; 33.8], p<0.001; –0.4 (–0.7; –0.1), p=0.009; 4.2 (2.5; 5.9), p<0.001; –0.1 [–0.2; 0.0], p=0.027). Hemolysis was similar in subjects with Rf>8% vs. ≤8%. Explorative data on survival showed comparable results in the femoro-jugular and the jugulo-femoral group (81% vs. 72%, p=0.455). Conclusion: VV ECMO with femoro-jugular configuration caused less recirculation. Further risk factors for higher Rf were shorter distance between the two cannula tips, higher ECMO flow, and lower heart rate. Rf did not affect hemolysis.